Bovine Babesiosis Diagnosed in Formalin-Fixed, Paraffin-Embedded Tissues by Using In Situ Hybridization. Issue 6 (November 2020) - Hülskötter, Kirsten; Pfankuche, Vanessa M.; van Dyck, Lydia; Höltershinken, Martin; Springer, Andrea; Lienhart, Fabienne; Ermel, Sandra; Rehage, Jürgen; Hoedemarker, Martina; Strube, Christina; Hirzmann, Jörg; Bauer, Christian; et al.
Bovine babesiosis, caused by Babesia divergens, is in general a rare disease in Europe. Nonetheless, local outbreaks can cause severe economic damage, and postmortem identification represents a diagnostic challenge. During a recent outbreak in May 2018 in northern Germany, 21 animals of a herd of 150 cattle died within 40 days having had clinical signs of fever and hemoglobinuria. Gross examination of 4 of the 21 deceased animals revealed a tick infestation, jaundice, and dark brown staining of urine and kidneys. Histologically, there were iron-positive deposits, hyperplasia of the red pulp of the spleen, and centrilobular necrosis of hepatocytes. In several locations, small basophilic granules suggestive of intraerythrocytic parasites were visible in hematoxylin-eosin- and Giemsa-stained sections. Peripheral blood smears from a living cow from the herd and polymerase chain reaction (PCR) of feeding ticks revealed B. divergens infection. In situ hybridization (ISH) was applied on formalin-fixed, paraffin-embedded (FFPE) tissue of the necropsied cattle to confirm babesiosis in these animals postmortem. Digoxigenin-labeled DNA probes were generated based on a specific nucleotide sequence for B. divergens, obtained by PCR and sequencing of DNA isolates from infected Ixodes ricinus ticks from deceased cattle. ISH using these probes allowed postmortem diagnosis of B. divergens infection in routinely fixed FFPE tissues.